Management of Intravenous Infiltration Injuries. Issue 6 (December 2019) - Massand, Sameer; Carr, Logan; Schneider, Emily; Johnson, T. Shane
Abstract : Background: Intravenous (IV) lines are ubiquitous in hospital settings. These lines can malfunction, leaking noxious contents into subcutaneous tissue. Existing literature describes invasive intervention and complex treatment protocols. These persist despite significant changes in the composition and administration of IV agents. The purpose of this study is to examine the consequences of IV infiltrations at a tertiary medical center to update protocols and treatment algorithms. Materials and Methods: This study is an observational, retrospective chart review performed at a tertiary care medical center. All inpatient plastic surgery consultations for IV infiltration were reviewed from 2011 to 2017. Patients were included if IV infiltration was suspected or documented. Data were collected for each injury regarding patient demographics, substance, and intervention. Results: The plastic surgery service evaluated 381 IV infiltration injuries from 2011 to 2017, with 363 meeting the criteria. Injuries per year progressively increased, with 32 consultations in 2011 and 102 consultations in 2017. The vast majority of injuries identified (91%) were treated with only elevation and observation. The minority consisted of wound care (7%) performed by nursing or any form of incision, aspiration, or antidote injection (2%) performed by the physician. Of the 363 injuries, the most common infiltrates were noncytotoxic (35%), radiographic contrast (27%), and known vesicants (18%). Interestingly, a large portion of consultations were requested by other surgical services (32%). Conclusions: Although there is an increase in expert involvement for cases of IV infiltration injuries, the vast majority of these injuries are managed with minimal intervention. This is most likely owing to recent changes that have decreased the potential for harmful infiltration. Contrary to existing literature, invasive intervention is almost never indicated.